Particle morphology influence on mechanical and biocompatibility properties of injection molded Ti alloy powder - (:unkn) unknown (IOS PRESS, 2014)
Titanium and Titanium alloys exhibits properties that are excellent for various bio-applications. Metal injection molding is a processing route that offers reduction in costs, with the added advantage of near net-shape components. Different physical properties of Titanium alloy powders, shaped and processed via injection molding can achieve high complexity of part geometry with mechanical and bioactivity properties, similar or superior to wrought material. This study describes that the effect of particle morphology on the microstructural, mechanical and biocompatibility properties of injection molded Ti-6Al-4V (Ti64) alloy powder for biomaterials applications. Ti64 powders irregular and spherical in shape were injection molded with wax based binder. Binder debinding was performed in solvent and thermal method. After debinding the samples were sintered under high vacuum. Metallographic studies were determined to densification and the corresponding microstructural changes. Sintered samples were immersed in a simulated body fluid (SBF) with elemental concentrations that were comparable to those of human blood plasma for a total period of 15 days. Both materials were implanted in fibroblast culture for biocompatibility evaluations were carried out. The results show that spherical and irregular powder could be sintered to a maximum theoretical density. Maximum tensile strength was obtained for spherical shape powder sintered. The tensile strength of the irregular shape powder sintered at the same temperature was lower due to higher porosity. Finally, mechanical tests show that the irregular shape powder has lower mechanical properties than spherical shape powder. The sintered irregular Ti64 powder exhibited better biocompatibility than sintered spherical Ti64 powder. Results of study showed that sintered spherical and irregular Ti64 powders exhibited high mechanical properties and good biocompatibility properties.
Keywords: Sintering; powder injection molding; titanium alloy; biocompatibility; GAS; COMPONENTS